Fertilization, Oocyte Activation, Calcium Release and Epigenetic Remodelling: Lessons From Cancer Models - Shafqat, Areez; Kashir, Junaid; Alsalameh, Sulaiman; Alkattan, Khaled; Yaqinuddin, Ahmed (Frontiers in Cell and Developmental Biology, 2022)
Oocyte activation deficiency (OAD) is the basis of Total Fertilization Failures (TFF) and is attributed to mutations in the PLCζ gene – termed male factor infertility. This derives abnormal Ca2+ oscillations and could be the main cause of primary disruptions in the gene expression of Ca2+-related proteins. Epigenetic mechanisms are universally accepted as key regulators of gene expression. However, epigenetic dysregulations have not been considered as potential mechanisms of oocyte-borne OAD. Herein, we discuss changes in DNA methylome during oogenesis and embryogenesis. We further highlight key pathways comprising the oocyte Ca2+ toolkit, which could be targets of epigenetic alterations, especially aberrations in DNA methylation . This perspective highlights the intricate link between DNA methylation and Ca2+ signaling in somatic cells by bringing forward evidence from cancer research, further warranting an investigation into this intriguing relationship in oocytes. From a therapeutic standpoint, if our hypothesis is proven to be correct, this will explain the cause of TFF in idiopathic cases and will open doors for novel therapeutic targets.